(untitled) (Journal of Computational Mathematics, 1991)
A system E:C^n→ C^n is said to be an exponential one if its terms are ae^im_1Z_1.… .e^im_nZ_n. This paper proves that for almost every exponential system E:C^n→ C^n with degree (q_1,…,q_n), E has exactly Π^n_j=1(2q_j) zeroes in the domain D={(Z_1,…,Z_n)C^n:Z_j=x_j+iy_j,x_j,y_jR,0≤ x_j